2022
DOI: 10.46281/ijmri.v6i1.1581
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Uses of Event Marketing Strategy as the Experiential Marketing Strategy of Bank: A Study on a Commercial Bank Limited

Abstract: The study investigates is to analyze the uses of event marketing of a bank: A study on a commercial bank. To identify the uses of event marketing as experiential marketing in the banking sector is present in Bangladesh. It is clear that event marketing makes the bank more profitable than other advertising strategies because it can grasp client attention than other marketing strategies. Event marketing can increase loans more than other advertising strategies. Event marketing strategy is that given greater cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Özkaynar (2022) argued that banks' marketing strategies had to incorporate new technologies such as the Metaverse, Blockchain, and Cryptocurrency. Islam et al (2022) indicated that banks could gain more from event marketing than traditional advertising because the former could generate more attention than the latter. Simultaneously, Uksumenko et al (2017) asserted that banks needed to adapt themselves to the fast changes and made use of digital marketing services such as Internet banking, mobile banking, and ATM, to connect their customers, which could help banks promote their products effectively and reach their marketing goals (Nguru et al 2017).…”
Section: Marketing Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Özkaynar (2022) argued that banks' marketing strategies had to incorporate new technologies such as the Metaverse, Blockchain, and Cryptocurrency. Islam et al (2022) indicated that banks could gain more from event marketing than traditional advertising because the former could generate more attention than the latter. Simultaneously, Uksumenko et al (2017) asserted that banks needed to adapt themselves to the fast changes and made use of digital marketing services such as Internet banking, mobile banking, and ATM, to connect their customers, which could help banks promote their products effectively and reach their marketing goals (Nguru et al 2017).…”
Section: Marketing Strategymentioning
confidence: 99%
“…Event marketing makes the bank more profitable than other advertising strategies (Islam et al 2022).…”
mentioning
confidence: 99%